2015
DOI: 10.1039/c5ra17254c
|View full text |Cite
|
Sign up to set email alerts
|

Binding interaction of an anionic amino acid surfactant with bovine serum albumin: physicochemical and spectroscopic investigations combined with molecular docking study

Abstract: Exploration of binding interaction between anionic amino acid surfactant and BSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Dasmandal et al . 9 used molecular docking and spectroscopy experiments and found that the binding of anionic amino acid surfactant (AAS) to BSA occurred between hydrophobic subdomain IIA and IIIA where tryptophan-213 residue is located. They observed multiple hydrogen bonding and hydrophobic interactions between the AAS ligand and the BSA which agrees with the current study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dasmandal et al . 9 used molecular docking and spectroscopy experiments and found that the binding of anionic amino acid surfactant (AAS) to BSA occurred between hydrophobic subdomain IIA and IIIA where tryptophan-213 residue is located. They observed multiple hydrogen bonding and hydrophobic interactions between the AAS ligand and the BSA which agrees with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine Serum Albumin (BSA) is an abundant plasma protein and a universal bio-reagent used in numerous applications, such as enzyme linked immunosorbent assays and immunofluorescence microscopy 2,4,9 . The crystal structure of BSA consists of three homologous domains, each in turn is divided into sub-domain A and B 6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the serum albumins, BSA has been widely used in biophysical studies to clarifying the binding mechanism of small molecules to proteins due to its physiological functions and 76% of structural similarity with Human Serum Albumin (HSA) (Sułkowska, 2002;Dasmandal et al, 2015). Investigation on binding of drugs to serum albumins may help us to understand drug's distribution and toxicity in the biological systems.…”
Section: Introductionmentioning
confidence: 99%